PEMANFAATAN MEDIA PEMBELAJARAN INTERAKTIF DALAM KONSTRUKSI BANGUNAN - Alda Mutia Azzahra (CV. ADIBA AISHA AMIRA, 2023)
The utilization of interactive learning media in building construction education is becoming an increasingly important topic along with the development of technology. This abstract will discuss some of the main benefits of using interactive learning media in building construction education, such as increasing learning motivation, improving concept understanding, and facilitating independent learning, improving learning outcomes. This abstract will also discuss some examples of interactive learning media that can be used in building construction education, such as simulations, games, animated videos, and virtual reality (VR). The utilization of interactive learning media in building construction education has the potential to improve the quality of learning and help students achieve a better understanding of building construction concepts.